Design Language in Motorcycle Design - Pierre Yohanes Lubis (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2019)
Design language as a form of non-verbal communication is comprised of shapes, colour, texture, pattern, etc. These elements of design language are the penultimate way of communication for designers, especially industrial and product designers. It is the cue that guides the consumer on how to navigate and behave with a product. In relation with motorcycle design, the author investigated on the design language of various motorcycle designs, including how different types of motorcycles for different use could significantly alter the whole design language. This research was carried out with the elements of design language in mind in order to understand it a little further and how it can assist the design process.